Role of the VPS35 D620N mutation in Parkinson's disease. (March 2017) - Mohan, Megha; Mellick, George D.
Abstract: Parkinson's disease (PD) is a neurodegenerative disorder involving the loss of dopaminergic neurons in the brain. Following the discovery of the PD-causing D620N mutation in the VPS35 (Vacuolar sorting protein 35) gene, dysfunction in the subcellular retromer complex has been strongly implicated in pathogenesis of PD. Although the function and dysfunction of the retromer has been a focus of study for some time, the role of this complex in the development of PD is not fully understood. Investigating cellular alterations that occur when the retromer is rendered dysfunctional, such as when the D620N disease-causing mutation is introduced into various model systems, shows that endosomal processing defects are major contributors to the disease phenotype. Altered trafficking of retromer cargo molecules, reduced cellular survival and altered processing of alpha-synuclein have all been observed in the presence of the D620N mutation. In addition, interactions between the retromer and the protein products of other familial Parkinsonism-related genes, has made the retromer a prime target of research in PD. This review gives an overview of the changes in retromer function, identified thus far, that may contribute to the neurodegeneration observed in PD. Highlights: The VPS35 D620N mutation contributes to the pathogenesis of Parkinson's disease. VPS35 D620N mutations cause phenotypes similar to sporadic Parkinson's disease. Retromer dysfunctions cause protein trafficking defects in Parkinson's disease.